1977
DOI: 10.2172/5348997
|View full text |Cite
|
Sign up to set email alerts
|

Fission-product energy release for times following thermal-neutron fission of /sup 235/U between 2 and 14000 seconds

Abstract: 12. II. Copy Reproduction and Distribution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…7) It was found that the summation calculation based on it overestimated the -ray component, and largely underestimated the -ray component of the decay heat after a fission burst measured at Yayoi 14) and Oak Ridge. 15,16) The same kind of disagreement 17) was experienced also in the US (preliminary version of ENDF/B-V) 18) and in Europe. Yoshida and Nakasima 7) pointed out that the calculations based on the preliminary version of the JNDC FP Decay Data File were suffering from the pandemonium problem through the use of published decay schemes to derive the values of E and E for individual short-lived (or highly Q -valued) FP nuclides.…”
Section: Pandemonium Problem and Theoretical Correctionsmentioning
confidence: 82%
“…7) It was found that the summation calculation based on it overestimated the -ray component, and largely underestimated the -ray component of the decay heat after a fission burst measured at Yayoi 14) and Oak Ridge. 15,16) The same kind of disagreement 17) was experienced also in the US (preliminary version of ENDF/B-V) 18) and in Europe. Yoshida and Nakasima 7) pointed out that the calculations based on the preliminary version of the JNDC FP Decay Data File were suffering from the pandemonium problem through the use of published decay schemes to derive the values of E and E for individual short-lived (or highly Q -valued) FP nuclides.…”
Section: Pandemonium Problem and Theoretical Correctionsmentioning
confidence: 82%
“…The decay heats from 235 U thermal fission have been calculated with the ORIGEN-S code and compared with the measurements of ORNL [9]. Figure 2 shows comparisons of the decay heats with measurements and calculated results with different fission yields data.…”
Section: Resultsmentioning
confidence: 99%
“…The measured data are taken from those performed at Oak Ridge National Laboratory for 235 U and 239 Pu thermal neutron fission [1,2] and those at YAYOI of Tokyo University for 238 U fast neutron fission [6]. The nuclides of 235 U, 239 Pu, and 238 U are important fissioning nuclides in the decay heat analysis in a light water reactor.…”
Section: Comparison Of Decay Heat Calculation Using Jendl Jeff and mentioning
confidence: 99%
“…As there are many short-lived nuclides for which experimental difficulties are encountered, the accurate nuclear data are, in actuality, unavailable for such nuclides. Under such circumstance, integral measurements have been undertaken in order to acquire reliable values of the decay heat power covering short cooling times after fission [1][2][3][4][5][6][7][8][9]. These integral-measured decay heat power data are employed to assess the summation calculation using microscopic data, that is, the decay and fission yield data of fission products.…”
Section: Introductionmentioning
confidence: 99%